Functional characterization of orexin system - Chua, Peiling (2009)
Orexin, which has been known to be involved in feeding and sleep-wake cycle, might have antidepressant-like effects. Researches indicate that depression might be associated with nucleus accumbens and its dopaminergic inputs from ventral tegmental area, which make up the mesolimbic dopamine system. Hence, we wanted to construct orexin receptor knockout viral vectors and inject them in vivo into the mouse’s brain. We modified the cloning strategy from blunt ligation to addition of adaptor sequences to pSilencer vector. Also, currently there is an absence of a good behavioral paradigm which mimics major depression so we hope to develop one by applying chronic stress through forced swimming test, together with clomipramine, to male wild-type mice. However, the results were not on par with our assumptions as we presumed that the mice will develop depression-like symptoms after 7 days of treatment and we also did not manage to generate the viral vectors. In conclusion, the cloning process should be continued so that we would be able to conduct experiments to elucidate orexin’s antidepressant-like effects and perhaps the different effects brought by both orexin receptors. Also, more modifications should be done to the forced swimming test experiments in order to generate a good behavioral paradigm.